Paciente de sexo femenino de 46 años de edad con hipotiroidismo, hipertensión y obesidad - Bravo Medina, Ivana Yessenia (2019)
This clinical case is based on a 46 – year – old- female patient. Who was diagnosed 6 years ago with hypothyroidism and 4 years ago with hypertension, receives treatment for both diseases. It was referred to the nutrionist for presenting a nutritional disorder and excess weight in which it has been taking place for four months. In the results of the biochemical values performed are within the normal range. Regarding the nutritional assessment, a BMI of 33.5 kg/m2 was evidenced. (Obesity Grade l) The world health organization in 2009 emphasizes that there are worldwide statistc figures of 5 to 15% of people suffering from hypothyroidism, being moree likely in women than in men. The treatments of the disease consist of the adequate medication and the nutritional part that is very fundamental, so it requires a complete, varied, diet that will depend on your needs, both pthological and nutritional Hypertension is a crhonic pathology that consists in the increase in blood pressure caused by contraction of arterioles that normalize blood flow in the body, in wichthe heart has to pump blood through a very small space and pressure inside the blood vessels. The deficiency of the thyroid gland slows down the whole organism, causing hypertension in this case since the pressure-regulating mechanisms are altered; and excess weight in the individual that is characteristic of the disease or Disorder, it should be emphasized that it is always due to thyroid problems.